Prediction of marital commitment: Attachment style and Relational Maintenance Behavior - Ghezelseflo, Mehdi (Applied Family Therapy Journal (AFTJ), 2020)
Aims: The aim of the present study was to examine the role of relational maintenance behavior and attachment style in predicting marital commitment. Method: The statistical population was all people married in Tehran city that 372 married people (233 women and 139 men) were selected by multiple cluster sampling. The data collection instrument was Relational maintenance behavior measure (Stafford, Dainton, & Haas, 2000), Adult attachment questionnaire (Hazan, & Shaver, 1987), and personal commitment subscale from The Investment Model Scale (Rusbult, Martz & Agnew, 1998). Result: The results showed that there is a significant positive relationship between subscale assurance, openness, conflict management, share task, positivity, advice, and secure attachment with marital commitment and there is a significant negative correlative between avoidance and anxiety attachment style with marital commitment. Also, multiple regression analyses showed that four subscales relational maintenance behavior (assurance, openness, conflict management, and positivity) and attachment style (secure, avoidance and anxiety) can predict marital commitment (P=0.05). Conclusion: According to these findings, can conclude that relational maintenance behavior and attachment style impact marital commitment.